The Binding Prediction Model of The Iron-responsive Element Binding Protein and Iron-responsive Elements - Parikesit, Arli Aditya; Ramanto, Kevin Nathanael (Bioinformatics and Biomedical Research Journal, 2019)
Iron is essential to fulfilling an indispensable role in the biological process in human physiology. Various proteins were known involved in iron metabolism. One of the proteins called iron-responsive element binding protein (IRP)which acts as master iron of cellular iron homeostasis. There are two IRP known to date, which is: IRP1 and IRP2. Previous studies showed IRP bind to iron-responsive elements (IRE) located in 5’-UTR of the transferrin receptor 1. The interaction of IRP/IRE is well studied through many years to find a better treatment for the cellular disorder in iron metabolism. However, the structural differences of both IRP and the binding prediction model of IRP/IRE remain unclear. This study provides a better understanding of the IRP structure and the IRP/IRE2 binding prediction model in a healthy condition. Several bioinformatic analyses were implemented in this study, such as molecular docking simulation, domain prediction, and structural similarity analysis. Structural analysis of IRP demonstrates a low root mean square deviation score that indicates both of IRP have high similarity in structure with different characteristics, such as binding site, and metabolic pathway. Interestingly, molecular docking simulation showed IRP has a preferably binding site when targeting specific IRE. Thus, this information could be beneficial in developing a drug for an iron-related disease.